Significant Role of Procalcitonin and Proinflammatory Markers in Diabetic Foot Ulcer Infections - Gahlot, Dr. Ghanshyam; Ram, Dr. Poonma; Parmar, Dr. Dinesh; Garg, Dr. Manoj; Hundekar, Dr. Prakash; Aseri, Dr. R. K.; Mansuriya, Dr. B. L.; Kumar, Dr. Surendra (International Journal of Innovative Research in Medical Science, 2021)
Background: Procalcitonin (PCT), an amino acid protein precursor of calcitonin hormone released by thyroid C cells or other body cells, can be used as a marker for diagnosing infection. PCT has a suggestive role in diagnosing diabetic foot infection alone or in combination with other markers of infection. Aim: We aimed to evaluate the roles of interleukin-6 (IL-6), CRP, and PCT levels in the differential diagnosis of the patients with infected diabetic foot ulcer (IDFU) and non-infected diabetic foot ulcer (NIDFU) and to compare those with C-reactive protein (CRP), white blood cell (WBC), and erythrocyte sedimentation rate (ESR). Methods: A total of 95 subjects with DFU and NIDFU were enrolled. WBC count, ESR, CRP, and PCT were done for all subjects at admission after obtaining informed consent. Patients over 18 years with a diagnosis of type 2 diabetes mellitus and DFU who were followed up in our hospital were included in the study. In addition to this patient group, patients with diabetes but without DFU were determined as the control group. Results: Twenty nine patients with IDFU, 29 patients with NIDFU, and 43 patients as the control group were included in the study. Fifty-six point three percent of the patients who participated in the study were males, and the mean age was 62.87 ± 10.99 years. WBC, ESR, CRP, and IL-6 levels of the cases with IDFU were determined to be significantly higher compared to the cases in NIDFU (p <0.001). The area under the ROC curve (AUROC) value was highest for CRP (p <0.001), and the best cut-oﬀ value for CRP was 36 m/L. The best cut-oﬀ values for IL-6, ESR, and WBC were 109.4 pg/mL, 53 mm/h, and 13.7 (103 μ/L), respectively. Conclusion: Serum PCT levels were not found to be eﬀective in the discrimination of IDFU and NIDFU. Serum IL-6 level seems to be one promising inﬂammatory markers in the discrimination of IDFU. Based on our results, we conclude that PCT has a valuable role in diagnosing infection in DFUs.